2018
DOI: 10.1186/s40557-018-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occupational injuries and the provision of safety and health information: data from the 4th Korean working conditions survey

Abstract: BackgroundThe aim of this study was to examine the relationship between the provision of safety and health information (PSHI) and occupational injuries.MethodsThis study was based on data from the 4th Korean Working Conditions Survey (KWCS) (2014). The sample consisted of data from 24,527 wage workers and was divided into high-risk and low-risk groups, depending on the probability of occupational injury. The high-risk group included subjects who could cause harm to themselves or others due to errors during wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Health and Safety Information (HSI): In accordance with Article 31 of the Occupational Safety and Health Act, employers should regularly provide information related to safety and health, including information on accident prevention, health management, disaster cases, and preventive measures. Previous studies demonstrated that there is a high probability of injury in the workplace when HSI is not provided, but few reports have examined the effects of such provision on mental health [ 29 ]. In response to the question, “Did you receive information regarding the health and safety risks associated with your job performance,” subjects were divided into those who were “Well-informed” and “Not informed.” If the job was associated with a risk of injury, the participant was asked whether information about the likelihood of mental and physical injury had been provided.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health and Safety Information (HSI): In accordance with Article 31 of the Occupational Safety and Health Act, employers should regularly provide information related to safety and health, including information on accident prevention, health management, disaster cases, and preventive measures. Previous studies demonstrated that there is a high probability of injury in the workplace when HSI is not provided, but few reports have examined the effects of such provision on mental health [ 29 ]. In response to the question, “Did you receive information regarding the health and safety risks associated with your job performance,” subjects were divided into those who were “Well-informed” and “Not informed.” If the job was associated with a risk of injury, the participant was asked whether information about the likelihood of mental and physical injury had been provided.…”
Section: Methodsmentioning
confidence: 99%
“…However, a survey on emotional labor and harassment in the workplace in 2019, which was conducted a year after the law was implemented, found that 70% of 2765 emotional workers said they were unprotected. Most research and intervention regarding HSI focuses on manufacturing or secondary industries [ 1 ] and rarely targets pink-collar workers [ 29 ]. There is also a lack of research examining the link between HSI and mental health [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Korea Occupational Safety and Health Agency (KOSHA) has benchmarked the European Working Conditions Survey and has adopted a Korean version of the Working Conditions Survey (KWCS). The first and second surveys were conducted in four-year cycles, and the cycle was changed to one year in the third survey [ 11 ]. However, considering the nature of the survey and the sensitivity of the analytical results, the cycle was changed to three years from the fourth survey [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first and second surveys were conducted in four-year cycles, and the cycle was changed to one year in the third survey [ 11 ]. However, considering the nature of the survey and the sensitivity of the analytical results, the cycle was changed to three years from the fourth survey [ 11 ]. The KWCS is conducted through interviews with employees and self-employed individuals regarding key issues about work, employment, and occupational health and safety, to present results about working conditions.…”
Section: Introductionmentioning
confidence: 99%